Institutionalisation of shariah governance practices: loosely coupling as a catalyst to evolutionary change - Salleh, Salina; Mohd Alwi, Norhayati; Mohd Ariffin, Noraini (2025)
This study examines the institutionalisation of Shariah governance practices within Islamic financial institutions (IFIs), focusing on EMERALD an Islamic bank in Malaysia. Anchored in institutional theory and the processual framework of Burns and Scapens (2000), the study analyses how Bank Negara Malaysia (BNM) regulatory, Shariah principle and institutional demands converge within a complex institutional setting. Empirical data were collected through nine in-depth interviews, extensive document analysis, and NVivo-assisted thematic interpretation. This study investigates EMERALD’s response to BNM’s Shariah Governance Policy Document (SGPD) 2019. The findings indicate that the institutionalisation of Shariah governance practices in EMERALD was undertaken to ensure Shariah compliance as a sustained institutional outcome. This evolutionary process involved the encoding of new rules under the Shariah Governance Policy Document (SGPD) 2019, internal enactment through interpretive mechanisms such as ijtihad, negotiated adaptation among institutional members, and gradual routinisation. Loose coupling functioned as a catalyst in this transformation, enabling compliance with regulatory expectations while preserving interpretive discretion and operational flexibility across governance realms. The study contributes to the understanding of how Islamic financial institutions (IFIs) respond to competing institutional demands by adapting internal structures and building consensus to institutionalise Shariah governance practices aimed at compliance. It also underscores the importance of consultative regulatory approaches and internal capacity-building in embedding Shariah-compliant practices. These insights are pertinent for regulators and practitioners seeking to align religious obligations with effective institutional governance.